On the Importance of Decarbonylation as a Side‐Reaction in the Ruthenium‐Catalysed Dehydrogenation of Alcohols: A Combined Experimental and Density Functional Study. Issue 14 (5th March 2014) - Sieffert, Nicolas; Réocreux, Romain; Lorusso, Patrizia; Cole‐Hamilton, David J.; Bühl, Michael
Abstract We report a density functional study (B97‐D2 level) of the mechanism(s) operating in the alcohol decarbonylation that occurs as an important side‐reaction during dehydrogenation catalysed by [RuH2(H2)(PPh3)3]. By using MeOH as the substrate, three distinct pathways have been fully characterised involving either neutral tris‐ or bis‐phosphines or anionic bis‐phosphine complexes after deprotonation. α‐Agostic formaldehyde and formyl complexes are key intermediates, and the computed rate‐limiting barriers are similar between the various decarbonylation and dehydrogenation paths. The key steps have also been studied for reactions involving EtOH and iPrOH as substrates, rationalising the known resistance of the latter towards decarbonylation. Kinetic isotope effects (KIEs) were predicted computationally for all pathways and studied experimentally for one specific decarbonylation path designed to start from [RuH(OCH3)(PPh3)3]. From the good agreement between computed and experimental KIEs (observed kH/kD=4), the rate‐limiting step for methanol decarbonylation has been ascribed to the formation of the first agostic intermediate from a transient formaldehyde complex.